2017
DOI: 10.1080/00016357.2017.1357080
|View full text |Cite
|
Sign up to set email alerts
|

Is caries equally distributed in adults? A population-based cross-sectional study in Norway – the TOHNN-study

Abstract: Objectives: The aim of the study was to examine the prevalence and distribution of dental caries in an adult population and identify factors associated with being caries free. Material and methods: Data were collected from a randomized population sample in Northern Norway (N ¼ 1932; 988 women; mean age 47.0 years, SD 15.3). The study included a structured questionnaire and a clinical examination. The sum of enamel and dentine caries, DS 1-5 , formed the main outcome measures for caries prevalence. Results: Mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
32
1
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 28 publications
4
32
1
2
Order By: Relevance
“…In a study on Italian adults, on average 60% had caries lesions, and initial lesions were less common than dentin lesions [Carta et al, 2015]. The prevalence of dentin caries lesions in this study population (40%) is in line with previous studies on Finnish adults and in Nordic countries [Oscarson et al, 2017]. Previous studies have also reported the polarization of dentin caries among Finnish and Scandinavian populations Tanner et al, 2013;Stecksén-Blicks et al, 2014;Oscarson et al, 2017].…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…In a study on Italian adults, on average 60% had caries lesions, and initial lesions were less common than dentin lesions [Carta et al, 2015]. The prevalence of dentin caries lesions in this study population (40%) is in line with previous studies on Finnish adults and in Nordic countries [Oscarson et al, 2017]. Previous studies have also reported the polarization of dentin caries among Finnish and Scandinavian populations Tanner et al, 2013;Stecksén-Blicks et al, 2014;Oscarson et al, 2017].…”
Section: Discussionsupporting
confidence: 76%
“…The prevalence of dentin caries lesions in this study population (40%) is in line with previous studies on Finnish adults and in Nordic countries [Oscarson et al, 2017]. Previous studies have also reported the polarization of dentin caries among Finnish and Scandinavian populations Tanner et al, 2013;Stecksén-Blicks et al, 2014;Oscarson et al, 2017]. The polarization is highly alarming, since it demonstrates that a small group of middle-aged people carry most of the current dentin caries burden.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Accordingly, untreated dental caries is a major economic burden for individuals and public health services (Kassebaum et al., , ). It is well known that there is a great disparity with regard to distribution of dental caries, mostly by social standing and associated differences in diet, use of fluorides and social empowerment (Edelstein, ; Meyer et al., ; Oscarson, Espelid, & Jönsson, ; Selwitz, Ismail, & Pitts, ). In a recent cross‐sectional study in Norway, Oscarson et al.…”
Section: Introductionmentioning
confidence: 99%
“…() found that living in a rural area, low socioeconomic status, less frequent tooth cleaning and sugar containing soft drinks were associated with a higher prevalence of dental caries. Therefore, the development of more selective prevention concepts for these populations with strong caries incidence remains a major goal in contemporary preventive dentistry (Edelstein, ; Meyer et al., ; Oscarson et al., ). In these high‐risk patients, supportive antimicrobial measures may be useful in daily oral hygiene practice in addition to mechanical removal of biofilms and use of anticariogenic agents, for example, fluoride (ten Cate, ).…”
Section: Introductionmentioning
confidence: 99%